Vitamin D Supplementation in Infertile Men: Beyond Pooled Effects—A Critical Meta-Analysis of Heterogeneous Clinical Responses - Dragoș Puia; Marius Ivănuță; Mihaela Corlade-Andrei; Hicham Tory; Adrian-Gabriel Majeru; Bogdan Doroftei; Ramona Ștefăniu; Vlad Cristiana Elena; Cătălin Pricop (Endocrines, 2026)
Introduction: Male infertility is a complex global health challenge, with emerging evidence suggesting that vitamin D plays a pivotal role in testicular function and spermatogenesis. This systematic review and meta-analysis aimed to evaluate the impact of vitamin D supplementation on semen parameters and reproductive hormones in infertile men. Methods: A comprehensive search of electronic databases (PubMed, Cochrane Library, and Web of Science) was conducted to identify randomized controlled trials (RCTs) investigating vitamin D supplementation in infertile males. Primary outcomes included Follicle-Stimulating Hormone (FSH), total testosterone, and Sex Hormone-Binding Globulin (SHBG). Secondary outcomes focused on semen quality, specifically volume, concentration, and motility. Data were pooled using fixed-effects or random-effects models based on heterogeneity (I2). Results: Analysis of six trials (n = 696) revealed that vitamin D supplementation significantly increased total testosterone levels compared to controls (SMD: 0.38; 95% CI: 0.13, 0.62; p = 0.002), with no statistical heterogeneity (I2 = 0%). In contrast, no significant differences were observed for FSH (SMD: 0.01; 95% CI: −0.28, 0.29; p = 0.96) or SHBG (SMD: 0.95; 95% CI: −0.12, 2.02; p = 0.08). For semen parameters, supplementation was associated with notable improvements in sperm concentration and progressive motility, whereas semen volume remained largely unchanged across the included studies. High heterogeneity in SHBG results (I2 = 91%) suggests that individual study characteristics, such as baseline vitamin D deficiency, may influence hormonal responses. Conclusions: Vitamin D supplementation selectively enhances endocrine function by increasing testosterone levels and improves functional semen parameters in infertile men. These findings support the use of vitamin D as a cost-effective adjuvant therapy, though its impact on definitive fertility outcomes, such as live birth rates, requires further large-scale clinical investigation.